Post a New Question

Mathematics

posted by .

How would I express sin^6 theta in multiples of cos theta?

Thanks

  • Mathematics -

    sin^6 theta
    =(1-cos²(θ))³
    =1-3cos²(θ)+3cos^4(θ)-cos^6(θ)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Optimization

    min 2x+y subject to: x+y+z=1 and y^2+z^2=4 Any help would greatly be apprecaited. y^2+z^2=4 ---> put y = 2 cos(theta) and z = 2 sin(theta) x+y+z=1 ----> x = 1-2(cos(theta) + sin(theta)) 2x + y = 2 - 2 cos(theta) - 4 sin(theta) …
  2. algebra

    Can someone please help me do this problem?
  3. Trig

    Which expression equivalent to: cos(theta + pi/2). A)cos theta B)-cos theta C)sin theta D)-sin theta my book doesnt give examples of this but my crack at it would be C b/c distributive property?
  4. Calculus

    I wanted to confirm that I solved these problems correctly (we had to convert the polar curves to Cartesian equations). 1.rcos(theta)=1 x=1 2.r=2*sin(theta)+2*cos(theta) r^2=2rsin(theta)+2rcos(theta) x^2+y^2=2y+2x (a little unsure …
  5. trigonomtry

    can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
  6. trigonometry

    can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
  7. trigonometry

    can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
  8. Algebra II

    Multiple Choice Which expression is NOT equivalent to 1?
  9. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …
  10. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …

More Similar Questions

Post a New Question